How do GPs use x rays to manage chronic knee pain in the elderly? A case study. Issue 5 (1st May 2003) - Bedson, J; Jordan, K; Croft, P
Abstract : Objectives: To determine whether clinical signs and symptoms of osteoarthritis influence general practitioners' (GPs) decisions about x raying older patients with knee pain and whether x ray reports alter their initial treatment or referral plan. Methods: A cross sectional survey of 1000 GPs in England and Wales using "paper cases" in three questionnaires mailed at two-weekly intervals. The first questionnaire assessed GPs' management of patients with knee pain using four case scenarios, two with features of clinical knee osteoarthritis. The second questionnaire contained the same scenarios with information on x ray findings added. The third questionnaire considered management of knee pain in general. Results: 447 GPs responded to questionnaire 1, 316 (71%) to questionnaire 2, 287 (64%) to questionnaire 3. 106 responders (25%) would have x rayed all four patients and 64 (15%) none. Choosing to carry out an x ray examination was not influenced by the presence of clinical signs and symptoms of osteoarthritis but was linked to other management choices, such as referral to orthopaedics (odds ratio (OR) 2.13; 95% confidence interval (CI) 1.62 to 2.81). The strongest predictor in questionnaire 2 of a treatment or referral was whether it had been chosen in the first survey. However, the x ray report was associated with a significant change in treatment and referrals. Where radiographic osteoarthritis was present, GPs were less likely to refer to a physiotherapist (OR 0.64; 95% CI 0.50 to 0.83) or rheumatologist (OR 0.15; 95% CI 0.08 to 0.28), and more likely to refer to an orthopaedic surgeon (OR 31.34; 95% CI 21.51 to 45.66). Questionnaire 3 showed that GPs' general views on the use of x rays correlated with the frequency of their choosing to x ray in the four individual case scenarios. Conclusions: A GP's choice to x ray older people with knee symptoms is linked with decisions on treatment and referral even before the x ray result is known, but it does not appear to be influenced by clinical features of osteoarthritis. The presence of radiographic osteoarthritis has a marked impact on the decision to refer to secondary care. More evidence on the outcome of management without x rays is needed to help GPs in decision making.